A Perspective on Paleoindian Research from the Opposite End of the Foraging Spectrum. (3rd July 2018) - Thompson, Victor D.
ABSTRACT: This essay is a perspective on Paleoindian research examining the nature of this body of scholarship and how it is perceived by outside scholars. The discussion revolves around three different tropes in Paleoindian literature: (1) chronology and settlement research; (2) technology studies; (3) behavioral and ecological theory. While the studies that make up these tropes are not inherently invalid or bad, the focus on similar problems by a wide range of researchers seems to have limited Paleoindian scholarship to some degree. The intent of this essay is to provide scholars with a discussion piece regarding how their scholarship is perceived by outsiders and thus offer a departure point for debate regarding future trajectories of Paleoindian research.